Literasi Pengelolaan Keuangan IKM Anggota Forum Komunikasi Pelaku Usaha di Kabupaten Malang - Noya, Sunday; Ekawati, Yurida; Oktiarso, Teguh; Hadi, Yuswono; ,, Purnomo; Putrianto, Novenda Kartika (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
Although considered as one of the main drivers of the national economy, SMEs are very vulnerable to business competition. Limited access to resources including knowledge resources makes SMEs constrained to develop their support system. One of the obstacles faced by SMEs today is their limited grasp to the business financial management concept. They also have a difficulty in accessing a simple financial accounting application that fit to their business conditions. The community service program implemented by the Ma Chung Abdimas Grant Team aims to improve the financial literacy of SME members of Forum Komunikasi Pelaku Usaha in Kabupaten Malang, as well as their access to computer-based financial accounting application. This program is implemented in the form of training and mentoring to improve SME’s understanding and skills in financial management. The results concluded that the training program was effective. It is able to improve financial management literacy for IKM partners.